Evaluasi Usability Aplikasi Mobile Malang KER! Menggunakan Metode Heuristic Evaluation - Ardiansyah Dwi Cahyo; Herman Tolle; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Malang KER! is an android-based mobile application developed by DISKOMINFO Malang City to simplify services by providing data and information online. Based on the results of interviews with DISKOMINFO Malang City, it is known that there are several user complaints related to usability aspects, namely errors and satisfaction. Since the release of the Malang KER! Application It is known that DISKOMINFO has never evaluated usability on the application user interface. The existence of usability problems can reduce user productivity and comfort when using the application. Therefore, to find and solve usability problems, it is necessary to evaluate the user interface. Heuristic Evaluation is a usability evaluation method that involves an expert as an evaluator to find usability problems using the heuristic usability principle. The heuristic usability principle in this study uses 9 principles proposed by Monroy. Each usability problem found is given a severity rating on a scale of 0-4. The evaluation is carried out in two stages. Stage 1 uses the original application as an object and produces 18 findings of usability problems. Recommendations for improvement are made in the form of wireframes and highfidelity prototypes that refer to the advice evaluators and also guidelines. Evaluation of phase 2 uses the design of improvements that have been made as objects and produces 3 problems of usability. Which consists of 1 new usability problem and 2 usability problems that have not been lost but the severity rating is reduced.